Application of the ASPT Indices in biological rapid assessment of water quality in Dong Thap Muoi wetland area - Thanh, Nguyen Vu; Thinh, Ta Huy; Trong, Pham Dinh; Canh, Doan (Academia Journal of Biology, 2015)
Using benthic invertebrates such as macrobenthic and meiobenthic communities for assessment of the water quality is an effective rapid biological monitoring method. At present in Vietnam, the BMWP Score has been applied successfully at some scientific and applied research centers, as well as Hanoi State University, Institute of Ecology and biological Resources, Institute of Tropical Biology and other organizations. The present paper has approached two objectives: (i) Determining the benthic invertebrate composition at 33 sampling sites including freshwater insect larvae, annelids and mollusks and freshwater freeliving nematodes and (ii) Establishing the BMWP Score with ASPT indices in assessment of the water quality level at each other site from the all monitored stations. Here are 29 insect families, 19 annelid and mollusk families and 21 families of the freeliving nematodes which have been recorded. The 13 unknown macroinvertebrate families have been added to the BMWP VIETNAM Score. Analyzing result showed that in the Dongthapmuoi wetland ecosystem, the ASPT Indices at 27 investigating stations are moderatelly low and ASPT’s measures equivalent to 3.2 (3.0-4.7) level and surface water in this region has a pollution b mesosaprobe quality. In other 6 points, the ASPT indices are lower than in previous stations, equivalent to 1.5-2.7 level and surface water has a bad quality-very pollution (Polysaprobe). The ASPT index has been applied successfully for biological assessment of water quality of the riverbeds in Vietnam.